The Usage of Games in the Classroom and Kinesthetic Students’ English Achievement - Rantung, Fanny Helda (11th International Scholars Conference, 2017)
This study aimed to see whether there was a correlation between the usage of games in the classroom (in term of students’ involvement in games activities) and English achievement of the students with kinesthetic learning style. The 53 kinesthetic students, 26 males and 27 females, were the respondents of this study. The instruments were the questionnaires of Reid (1995) with 30 items on learning style and self-constructed based on the theory and literature of Wright, Betteridge, and Buckby (2006) with 15 items which were related to the usage of games in the classroom. Purposive sampling method was used to gather the data. The result of this study revealed that there was a significant correlation between the usage of games in the classroom and kinesthetic students’ English achievement. But there was no significant difference of kinesthetic students’ English achievement based on gender. Besides, the average level of kinesthetic students’ English achievement was in a good level. It is recommended that the usage of games in the classroom can be used as a good strategy for students to learn English.